Filogenetik Jenis-jenis Annonaceae dari Jawa Timur Koleksi Kebun Raya Purwodadi Berdasarkan Coding dan Non-coding sekuen DNA - Dewi Ayu Lestari; Rodiyati Azrianingsih; H. Hendrian (Universitas Gadjah Mada, 2018)
Annonaceae species of Purwodadi Botanic Garden collections from East Java encountered problems in species identification based on morphological characters. In addition, the unavailability of molecular data to support identification based on morphological characters hinders accurate identification of species. The aim of this research is to discern phylogenetic of Annonaceae species from East Java collections of Purwodadi Botanic Garden based on coding and non-coding sequence DNA. Annonaceae species used in this study are 30 species, includes outgroup from family of Magnoliaceae. Materials for DNA analysis were young leaves which were processed through DNA extraction, DNA amplification through PCR technique, DNA sequencing and data analysis with Maximum Likelihood (ML), Maximum Parsimony (MP) and Neighbour-Joining (NJ) method analysis. The results show that phylogenetic tree is divided into two subfamilies, i.e. Annonoideae and Malmeoideae. The topology of phylogenetic tree from three DNA molecular marker shows that non-coding sequence DNA (trnL-F molecular marker) has the best grouping of relationship and be able to explain the relationship between species of Annonaceae than rbcL and matK molecular marker as coding sequence DNA. Bootstrap value of trnL-F tree is very weak to high (36-100%) while rbcL is very weak to weak (17-63%) and matK tree is high (98-99%).